2001
DOI: 10.1093/toxsci/64.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility and Persistence of Di-2-ethylhexyl Phthalate (DEHP)- and Phenobarbital-Induced Hepatocellular Changes in Rodents

Abstract: The tumor promotion stage of chemical carcinogenesis has been shown to exhibit a persistence of cellular effects during treatment and the reversibility of these changes upon cessation of treatment. Inhibition of gap-junctional intercellular communication and increased replicative DNA synthesis appear to be important in this process. The present study assessed the persistence and reversibility of gap-junctional intercellular communication inhibition, peroxisomal proliferation, and replicative DNA synthesis in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…The relationship between the observed hepatic effects to PB treatment has been demonstrated in recovery studies in the rat where the effects of PB on liver weight, xenobiotic metabolizing enzymes and inhibition of gap junctional intercellular communication were reversible on cessation of treatment (Crampton et al, 1977; Isenberg et al, 2001; Lake et al, 1978). In addition, the liver lesions produced by PB in the mouse appear to be at least partially reversible.…”
Section: Resultsmentioning
confidence: 94%
“…The relationship between the observed hepatic effects to PB treatment has been demonstrated in recovery studies in the rat where the effects of PB on liver weight, xenobiotic metabolizing enzymes and inhibition of gap junctional intercellular communication were reversible on cessation of treatment (Crampton et al, 1977; Isenberg et al, 2001; Lake et al, 1978). In addition, the liver lesions produced by PB in the mouse appear to be at least partially reversible.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, the next objective was to determine whether inhibition of gap junctional intercellular communication was reversible, as was demonstrated in vivo (Isenberg et al, 2001). In these studies, inhibition of gap junctional intercellular communication was nearly completely reversed within 24 h of monoester removal.…”
Section: Discussionmentioning
confidence: 96%
“…For example, studies have shown that the increase in liver weight and cytochrome P450 enzyme activity induced by phenobarbital (Crampton et al, 1977;Lake et al, 1978) is reversible on cessation of treatment. The reversal of early non-neoplastic hepatic alterations has also been observed with other non-DNA reactive receptor mediated hepatocarcinogens such as metofluthrin (Deguchi et al, 2009);sulfoxaflor (LeBaron et al, 2013) and DEHP (Isenberg et al, 2001). Similarly, data generated for fluopyram demonstrated that the hepatic parameters induced following 28 and 90 days of treatment were reversible.…”
Section: Fluopyram Dose (Ppm)mentioning
confidence: 78%